(untitled) (Global Journal of Science Frontier Research, 2025)
The humanity has always been fascinated by the structure of the Earth it all started from the flat form and the further research resulted in acceptance of the sphere form The recent data allows us to determine the internal structure model of the planet according to indirect manifestations and measurement data This is the topic of this paper